Pengaruh Transfer Pricing dan Thin Capitalization terhadap Praktik Penghindaran Pajak - Elsha Fitri; Sany Dwita (Universitas Negeri Padang, 2023)
This study investigates the impact of thin capitalization and transfer pricing, along with the controls of firm size and profitability, on tax avoidance strategies in non-financial multinational firms for the years 2019–2022. The sample was determined by purposive sampling method and 32 non-financial multinational companies were obtained as samples. The data is panel regression data Panel regression data. The results of the study are that transfer pricing and thin capitalization have no effect on tax avoidance. Tax avoidance is influenced by the controlling factors of firm size and profitability. Future research can use research samples of multinational companies that are listed or not listed on the Indonesia Stock Exchange to produce more representative research.